IMPORTANCE OF GROWTH REGULATORE AND COLD STORAGE TREATMENTS FOR BREAKING OF GLADIOLUS (GLADIOLUS GRANDIFLORUS L.)CORM DORMANCY - G. B. BHUJBAL; N. G. CHAVAN; S. S. MEHETRE (The Bioscan, 2014)
The present experiment consisted of two genotypes viz., White Prosperity and Phule Neelrekha, four growth regulator treatments were GA3-125 ppm, BA- 50 ppm, NAA-100 ppm and control while five cold storage treatments viz., 6 weeks storage, 12 weeks storage, 18 weeks storage, 24 weeks storage and control. In the growth regulator GA3 125 ppm and in cold storage 24 week cold storage treatments was most effective in the breaking of dormancy and resulted in earlier sprouting. It concluded that Gladiolus corm dormancy will be break by the use of growth regulators and cold storage treatments